Evaluation Towards Government Assignment to State Owned Enterprise (SOE) on Sumatera Toll Road Operation for 2014-2019 Period - Priambodo, M Fakhry; Asnawi, Said Kelana; Muktiyanto, Ali (CV. Era Digital Nusantara, 2024)
Evaluation Towards Government Assignment to State Owned Enterprise (SOE) on Sumatera Toll Road Operation for 2014-2019 Period seeks to examine the impact of the government’s assignment to company’s financial performance during concession period. The object of research are Bakauheni-Terbanggi Besar section, Terbanggi Besar-Pematang Panggang-Kayu Agung section, Palembang-Indralaya section, Pekanbaru-Dumai section, and Medan-Binjai section.This study employs a quantitative research methodology with a case study approach, in which relevant literature is examined and the necessary secondary data is gathered. In order to ascertain if five toll road sections were feasible, analysis was done on previously gathered data using the following criteria: Net Present Value, Adjusted Present Value, Cost and Benefit Analysis, and Economic Benefit Analysis. The effects of the project on business performance and the viability of implementing a toll road project were then determined by balancing the results.From 5 sections, it was concluded that the Bakauheni-Terbanggi Besar, the Palembang-Indralaya and Medan-Binjai section provide additional value to the company's performance during concession period. These five sections offer substantial benefits that should be implemented based on the total economic benefits calculation. Long-term income uncertainty, financial restraints, high interest rates, inappropriate traffic volumes, operational costs that exceed planning, and low willingness to pay are all influencing factors.